PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KERJASAMA TIM SEBAGAI VARIABEL MEDIASI PADA PT KARYA PRIMA PUTERA PERKASA - Shodik, Muhammad Taqiyyuddin; Dihan, Fereshti Nurdiana (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research aims to determine the mediating influence of teamwork in the relationship between transformational leadership style, organizational culture and employee performance. This research uses a quantitative approach with data collection techniques using saturated samples, where the respondents in this research are the total population of the object studied, namely 50 people. As for distributing questionnaires using Google Forms to every employee who works at PT. Prima Putera Perkasa's work. The analysis method in this research uses SEM with the SmartPLS analysis tool. Meanwhile, the results of this research show that directly transformational leadership style and company culture do not have a significant influence on employee performance. However, indirectly through teamwork, company culture has a significant influence on employee performance at PT. Prima Putera Perkasa's work.